LEXICAL ANALYSIS OF SEMANTIC ERRORS FOUND IN THE TRANSLATION OF JOKO WIDODO’S INSTAGRAM ACCOUNT - Ni Made Verayanti Utami; I Gusti Agung Sri Rwa Jayantini; Yupita Pratiwi (Universitas Muhammadiyah Semarang, 2021)
This research focuses on the semantic errors in lexis occurred in the translation by Instagram Machine Translation. This research aims at identifying the types of semantic error in lexis made by Instagram Machine Translation found in the Joko Widodo’s Instagram account. This research also analyses semantic errors in lexis to show how Instagram machine translation works and the potential errors that it may cause. This study utilized observation method in collecting the data. Descriptive qualitative method was applied in analyzing the semantic errors in lexis by elaborating each type of them. In addition, translation procedures were also examined to find out clear explanation on what procedures contribute to the errors. The data were taken from the posts in Joko Widodo’s Instagram account and were analyzed by the semantic errors in lexis based on theory by James (1998). The study concluded that the confusion of sense relations in choosing a wrong synonym is mostly found in the translation of Instagram machine translation.